"Your behaviour has consequences": Children and young people's perspectives on reparation with their fathers after domestic violence. (May 2018) - Lamb, Katie; Humphreys, Cathy; Hegarty, Kelsey
Abstract: This paper presents findings from qualitative research undertaken in Australia with children and young people who have experienced domestic violence aged 9 to 19 years. The aim was to explore children and young people's perspectives on fathering in the context of domestic violence as well as the key messages they believe fathers who attend a program to address their violence need to know. This paper will focus on some of the findings of the study, with a particular focus on the issue of reparation which was identified as a strong theme in children and young people's accounts. Highlights: Children and young people described wanting to engage in a process of reparation with their fathers after domestic violence. Reparation was considered important regardless of whether they wanted a relationship with their father into the future. Components of reparation described included: addressing the past, making a commitment to change and rebuilding trust.